A matlab program for diagnosis and adjustment of mix proportions of structural lightweight concrete - Abdullahi M.; Al-Mattarneh H.M.A.; Mohammed B.S. (EuroJournals, Inc., 2023)
The existing mix design codes of structural lightweight concrete are not capable of giving the mix compositions that meet the target requirements. They only give quantities for the first trial batch. Adjustment of the mix ingredient is required to achieve the response of interest. An advisor for mixture proportioning adjustment of structural lightweight concrete would alleviate these problems. Various textural sources were consulted to obtain information on adjustment of mix ingredients. A flow chart was developed and used to create an interactive graphical user interface in matlab environment. The program can diagnose the causes of failure of mix performance and give recommendation on necessary adjustment. EuroJournals Publishing, Inc. 2009.